Fiscal costs of climate change in the United States - Lint Barrage (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
This paper explores the fiscal impacts of climate change and their policy implications for the United States. I develop and empirically quantify a climate-macroeconomic model where climate change can affect (i) government consumption requirements (e.g., healthcare), (ii) transfer payments (e.g., income support), (iii) tax revenues, and where (iv) adaptation to sea level rise (e.g., sea walls) must be publicly financed. First, the paper presents a novel bottom-up quantification of fiscal costs based on literature synthesis and an empirical analysis of public healthcare costs associated with extreme temperatures and wildfires. Climate change is projected to increase total government consumption (transfer) requirements by around 2.2% (0.4%) by 2100 in a business-as-usual climate policy scenario, with healthcare accounting for the majority of cost increases. Second, I show theoretically that the social cost of carbon must account for climate impacts on both government consumption and household transfer payments if the marginal cost of public funds exceeds unity. Finally, the numerical results indicate that fiscal considerations are of first order importance for climate policy design. The elasticity of the social cost of carbon with respect to government consumption (transfer) impacts per degree warming is estimated to be around 20 (10). Accounting for fiscal considerations moreover increases the projected domestic U.S. welfare benefits of climate policy by up to a factor of three.
Keywords: 330; Klimawandel; Soziale Kosten; Öffentliche Ausgaben; USA